Reply to short communication 'Comment on "Numerical approach to define a thermodynamically equivalent material for the conjugate heat transfer simulation of very thin coating layers" by P. Olmeda, X. Margot, P. Quintero, J. Escalona, International Journal of Heat and Mass Transfer, Vol. 162(2020) 120377 " by Jaal Ghandhi and Georgios Koutsakis. (June 2021) - Olmeda, P.; Margot, X.; Quintero, P.; Escalona, J.
Highlights: Multi-factorial 1D heat transfer model allows defining thermodynamic properties. Mesh nodes and material thickness are critical to define a good equivalent material. A thick equivalent material behaves thermodynamically similarly to a very thin coating. 3D CHT of walls coated with thin insulating layers may be performed. Abstract: In the recent paper "Surface temperature of a multi-layer thermal barrier coated wall subject to an unsteady heat flux" by G. Koutsakis, G. F. Nellis, J. B. Ghandhi, Int. J. Heat Mass Transfer 155(2020), 119645 the authors have proposed an analytical solution to determine wall temperature of surfaces coated with multi-layer coatings. The solutions are obtained based on the assumptions of one-dimensional heat flux using the matrix method in conjunction with the 1-D Laplace transformed heat diffusion equation. The authors suggest that using this analytical approach a thicker pseudo-material could be found in order to address the 3D conjugate heat transfer problem. This approach is compared with another published methodology that employs a DoE (Design of experiments) in combination with a multiple regression analysis to define a thicker equivalent coating layer.